Networked Learning: Theorising a ‘Manager’ Capability - McMordie, Shane (Proceedings of the International Conference on Networked Learning, 2018)
Networked learning (NL) is concerned with how students learn using connections enabled by IT: connections with other learners, with teachers and with resources. In contrast to school or university education, there is no place in the current conceptual model of NL for an administration or management function. This may be demonstrated by looking at the proceedings of the Networked Learning Conference. The aim of this paper is to develop the conceptual model of NL by proposing a 'manager' capability. The method consists of critical discourse analysis of a sample of the Conference proceedings to gain a better understanding of the problem. This is followed by a pragmatic exercise in which suitable concepts from other relevant disciplines are identified, assessed and added to the NL conceptual model. The most likely explanation for the gap in the theory is the collective ontological stance of the NL research community.